1999
DOI: 10.1177/089686089901902s27
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Continuous Ambulatory Peritoneal Dialysis on Change in Serum Leptin

Abstract: Objective Elevated serum leptin can contribute to anorexia and poor nutrition in patients with chronic renal failure, because leptin is elevated in chronic renal failure patients with or without dialysis, especially in chronic ambulatory peritoneal dialysis (CAPO) patients. The aim of this study was to find whether leptin can be removed by peritoneal dialysis (PO) and to analyze factors that can affect serum leptin after start of CAPO by observing the change in serum leptin shortly after start of CAPO and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Nanayakkara et al presented negative linear association between eGFR and plasma leptin in patients with CKD (Nanayakkara et al, 2009). It has been reported that the start of PD treatment is associated with a marked increase in serum leptin levels (Kim et al, 1999;Teta et al, 2008). What is interesting is that leptin can be eliminated by PD.…”
Section: Discussionmentioning
confidence: 99%
“…Nanayakkara et al presented negative linear association between eGFR and plasma leptin in patients with CKD (Nanayakkara et al, 2009). It has been reported that the start of PD treatment is associated with a marked increase in serum leptin levels (Kim et al, 1999;Teta et al, 2008). What is interesting is that leptin can be eliminated by PD.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients undergoing renal replacement therapy, those treated by peritoneal dialysis (PD) have extraordinarily raised serum leptin, clearly out of proportion to the fat accumulation observed in these patients [2]. In addition, serum leptin increases by 189% within 1 month after starting PD treatment, in spite of significant leptin removal by the peritoneal route [3]. It is therefore probable that factors other than fat mass stimulate leptin production in PD.…”
Section: Introductionmentioning
confidence: 99%
“…Increase in adiposity is reported to be a source of inflammatory cytokines or adipokines, for example, leptin, which is increased in PD patients. 28 Leptin is also reported to have strong interaction with proinflammatory cytokines including interleukin-1 and tissue necrosis factor-α. 29 Finally, there are studies about persistent release of proinflammatory mediators in PD patients with maintenance or after an episode of peritonitis.…”
Section: Discussionmentioning
confidence: 99%